Pharmacovigilance in hospice/palliative care: Net effect of amitriptyline or nortriptyline on neuropathic pain: UTS/IMPACCT Rapid programme international consecutive cohort. (June 2022) - Hussein, Akram; Digges, Madeline; Chang, Sungwon; Hunt, Jane; Doogue, Matt; Rowett, Debra; Agar, Meera; Sinnarajah, Aynharan; Kain, Danielle; Allan, Simon; Boland, Jason W; Currow, David C
Background: Real-world effectiveness of interventions in palliative care need to be systematically quantified to inform patient/clinical decisions. Neuropathic pain is prevalent and difficult to palliate. Tricyclic antidepressants have an established role for some neuropathic pain aetiologies, but this is less clear in palliative care. Aim: To describe the real-world use and outcomes from amitriptyline or nortriptyline for neuropathic pain in palliative care. Design: An international, prospective, consecutive cohort post-marketing/phase IV/pharmacovigilance/quality improvement study of palliative care patients with neuropathic pain where the treating clinician had already made the decision to use a tricyclic antidepressant. Data were entered at set times: baseline, and days 7 and 14. Likert scales graded benefits and harms. Setting/participants: Twenty-one sites (inpatient, outpatient, community) participated in six countries between June 2016 and March 2019. Patients had clinician-diagnosed neuropathic pain. Results: One hundred and fifty patients were prescribed amitriptyline (110) or nortriptyline (40) of whom: 85% had cancer; mean age 73.2 years (SD 12.3); mean 0–4 scores for neuropathic pain at baseline were 1.8 (SD 1.0). By day 14, doses of amitriptyline were 57 mg (SD 21) and nortriptyline (48 mg (SD 21). Fifty-two (34.7%) patients had pain improvement by day 14 (amitriptyline (45/110 (43.3%); nortriptyline (7/40 (18.9%)). Thirty-nine (27.7%) had new harms; (amitriptyline 29/104 (27.9%); nortriptyline 10/37 (27.0%); dizziness ( n  = 23), dry mouth ( n  = 20), constipation ( n  = 14), urinary retention ( n  = 10)). Benefits without harms occurred (amitriptyline (26/104 (25.0%); nortriptyline (4/37 (10.8%)). Conclusions: Benefits favoured amitriptyline while harms were similar for both medications.